Answer:
x² – x – 12 = (x – 4)(x + 3)
Step-by-step explanation:
Identify two numbers that add to -1 and multiply to -12, let's call them p and q.
So ax² + bx + c = (x + p)(x + q)
pq = c
p + q = b.
It is easier to find these numbers by finding factors of -12.
This can be done by splitting the number up until all the numbers are prime.
-12 → 6 × -2 or -6 × 2 → -(3 × 2 × 2)
There can only be two numbers so the only options we have are 6 and -2, -6 and 2, 3, and -4, or -3 and 4.
We can eliminate them by adding them up.
6 + -2 = 4 ≠ -1 so that can't be it.
-6 + 2 = -4 ≠ -1 so that can't be it either.
-3 + 4 = 1 ≠ -1
therefore p and q are 3 and -4 because 3 + -4 = -1.
so x² – x – 12 = (x – 4)(x + 3)
p = -4, and q = 3.
(x – 4)(x + 3) = x(x + 3) – 4(x + 3) = x² + 3x – 4x + 12 = x² – x – 12